In situ Engineering of Hollow Porous Mo2C@C Nanoballs Derived From Giant Mo-Polydopamine Clusters as Highly Efficient Electrocatalysts for Hydrogen Evolution - Liu, Suli; Mu, Xueqin; Cheng, Ruilin; Lin, Shiyu; Zhu, Yang; Chen, Changyun; Mu, Shichun (Frontiers in Chemistry, 2020)
Low-cost nd highly effective catalysts are crucial to the electrocatalytic hydrogen evolution reaction (HER) and molybdenum carbides are a promising candidate because of their high reserves, stability, low cost, and structural diversity. In this work, we report a simple method to fabricate hollow porous Mo2C@C nanoball through a hydrothermal preparation of molybdenum precursors at high temperature. Specifically, we combined interfacial polymerization and chelation effect to synthesize the Mo-polydopamine (Mo-PDA) precursor. Then, the result shows that the Mo2C@C-3 only requires an ultralow Tafel slopes (∼55 mV dec-1) and low overpotential (∼167 mV) at 50 mA cm-2 in 0.5 M H2SO4 electrolyte, with long-term cycling stability. Besides, the Mo2C@C-3 also exhibits outstanding activity and stability under extensive HER tests in alkaline media. This study opens a new perspective for the development of highly porous molybdenum carbide-based materials for electrochemical applications.